702 PROGNOSTIC ROLE OF MYOCARDIAL VIABILITY ASSESSMENT BY 18F-FLUORODEOXYGLUCOSE POSITRON EMISSION TOMOGRAPHY IN STEMI PATIENTS WITH LATE PRESENTATION. (15th December 2022) - Denegri, Andrea; Gurgoglione, Filippo Luca; Magnani, Giulia; Montagna, Riccardo; Vignali, Luigi; Paoli, Giorgia; Graziani, Tiziano; Ruffini, Livia; Ardissino, Diego; Niccoli, Giampaolo
Abstract: Background: ST-segment elevation myocardial infarction (STEMI) is one of the world's leading causes of disability and death. The incidence of late-onset STEMI (i.e. after at least 12 hours from symptom onset to medical observation) accounts up to 10% of overall STEMI events and optimal management in this setting is still debated due to the lack of randomized data. The aim of the present study is to explore the usefulness of FDG-PET to improve late-onset STEMI treatment. Methods: We conducted a single-center retrospective observational study that included patients admitted for late-onset STEMI who underwent coronary angiography and FDG-PET to evaluate myocardial viability (MV). Follow-up by telephone interview and / or clinical follow-up at 6, 12, 24, 36, 48 and 60 months was performed in all patients. The prevalence of myocardial viability (MV) related to infarct-related artery (IRA) by FDG-PET study (using a semi-quantitative visual scoring method), the study of clinical and angiographic predictors of viability and the association of myocardial viability evaluated with FDG-PET with the improvement of the left ventricular ejection fraction (LVEF) were investigated. Results: A total of 27 patients with mean age 64.7 ± 11.1 years, predominantly men (n=25, 92, 6%), were enrolled in the study. Compared to patients without MV (n=12), MV-patients (n=15) presented more frequently dyslipidemia (100.0% vs 66.7%, p=0.015) and diabetes (53.3% vs 16.5%, p=0.050) but showed no difference in inflammatory biomarkers and echocardiographic parameters. Multivessel disease (MVD 86.7% vs 33.3%, p=0.004) and high-grade collateral-connection (hg-CC 80.0% vs 33.3%, p=0.027) were more frequent in MV-patients compared to patients without MV. The presence of angiographically visible hg-CC (OR=8.00, 95%CI 1.40-45.76, p=0.019) and MVD (OR=13.00, 95%CI 1.92-88.00, p<0.001) were positive predictors of FDG-PET MV related to IRA and remained independent positive predictors of FDG-PET MV related to IRA at multivariable logistic regression analysis (p<0.05). No significant differences were recorded between patients without MV and MV-patients in the incidence of MACEs (20.0% vs 50.0%, p=0.100). Of note, as compared to patients without MV, MV-patients displayed a significant improvement in LVEF (86.7% vs 50.0%, p = 0.036), with a higher mean value of LVEF at follow-up (39.4 ± 10.9 vs 29.6 ± 8.0, p = 0.013) and of LVEF change from baseline to follow-up (6.1 ± 7.2 vs -1.1 ± 9.1, p = 0.027). Conclusions: This study could be of great help in clinical practice in order to provide a personalized approach in patients with late-STEMI, suggesting the potential benefit of a routine assessment IRA-related viability by FDG-PET in all asymptomatic late-STEMI subjects and providing further evidence in favor of a revascularization of occluded IRA in those with documented myocardial viability.